On The Dominational Variants Of Some Degree Based Topological Indices (Journal of Pharmaceutical Negative Results, 2022)
Domination is an ancient graph theoretical topic with applications in psychology, political sci- ence, and human behaviour. A topological index is an area of graph theory that governs a compound’s molecular structure. This work aims to conglomerate the two different branches and determine the dominational variants of some celebrated degree based topological index. The newly described descriptors are generalised to standard graphs, corona products of graphs, and a few members of the windmill family of graphs in this study.